THE EFFECT OF TEAM ACCELERATED INSTRUCTION MODEL ON STUDENTS' TEXT ANALYSIS ABILITY IN GRADE VII - Batu Bara, Liza Handayani; Devianty, Rina (Universitas Muhammadiyah Mataram, 2025)
Analytical skills in understanding and interpreting news texts are essential in Indonesian language learning, particularly in shaping students’ critical thinking. Initial observations at SMP Negeri 29 Medan indicated that students still tended to understand texts literally and had difficulty distinguishing between facts and opinions. This study aims to determine the effect of the Team Accelerated Instruction (TAI) learning model on the analytical skills of seventh-grade students in interpreting news texts. The research employed a quantitative approach with a one-group pretest-posttest pre-experimental design. The sample consisted of 32 students from class VII-8, selected using the quota sampling technique. The instrument used was a multiple-choice test measuring the ability to identify facts and opinions, understand text structure, and evaluate the content of information. The results showed an increase in the average score from 48.91 to 70.31. The normality test indicated a normal data distribution (p > 0.05), and the paired t-test showed a significant difference (p = 0.000). The average N-Gain score of the 32 students was 0.4452, which falls into the “moderate” improvement category. These findings indicate that the TAI model not only significantly improves students’ analytical abilities but also contributes theoretically to supporting cooperative learning approaches based on social constructivism. Practically, TAI can serve as an alternative strategy for strengthening critical literacy in Indonesian language learning aligned with the Kurikulum Merdeka.